Spatial interrelations of Chinese housing markets: Spatial causality, convergence and diffusion - Gong, Yunlong; Hu, Jinxing; Boelhouwer, Peter (A+BE | Architecture and the Built Environment, 2018)
This paper comprehensively tests the spatial interrelationships of 10 housing markets in the Pan-Pearl River Delta (Pan-PRD) in China, including the properties of spatial causality, convergence and diffusion pa